Direct Transfer From the Referring Hospitals to the Catheterization Laboratory to Minimize Reperfusion Delays for Primary Percutaneous Coronary Intervention. (September 2015) - Anderson, Lindsay L.; French, William J.; Peng, S. Andrew; Vora, Amit N.; Henry, Timothy D.; Roe, Matthew T.; Kontos, Michael C.; Granger, Christopher B.; Bates, Eric R.; Hellkamp, Anne; Wang, Tracy Y.
<x xml:space="preserve">Abstract</x> Background— For patients with ST-segment–elevation myocardial infarction (STEMI) requiring interhospital transfer for primary percutaneous coronary intervention, direct transfer from the STEMI referral hospital to the catheterization laboratory (cath lab) at the STEMI receiving hospital may expedite reperfusion, but can be logistically challenging. Methods and Results— We studied 33 901 STEMI patients transferred for primary percutaneous coronary intervention in the Acute Coronary Treatment and Intervention Outcomes Network Registry–Get With The Guidelines from July 2008 to December 2012. The majority of patients were transferred directly to the cath lab (26 510 [78.2%]), and 7391 patients (21.8%) were transferred first to the hospital emergency department/ward. We observed significant interhospital variation in transfer patterns; only 21% of STEMI receiving hospitals routinely transferred >90% of STEMI patients to the cath lab directly. Compared with patients transferred first to the emergency department/ward, STEMI patients transferred to the cath lab had significantly lower first door-to-balloon times (median 191 versus 116 minutes, P<0.0001). After multivariable logistic regression, patients transferred directly to the cath lab also had lower adjusted mortality risk (odds ratio 0.58, 95% confidence interval 0.51–0.66, P<0.0001). Cardiogenic shock, heart failure signs/symptoms, and nonsystem reasons for reperfusion delay were present in 11%, 15%, and 28% of patients transferred first to the emergency department/ward, respectively. The association of direct cath lab transfer with lower mortality persisted after excluding patients with these reasons for delay to primary percutaneous coronary intervention (adjusted odds ratio 0.62, 95% confidence interval 0.46–0.84, P=0.002). Conclusions— Direct transfer of STEMI patients to the cath lab for primary percutaneous coronary intervention was associated with significantly faster reperfusion and lower mortality risk compared with transfer first to the emergency department/ward.